THE MORAL CONCEPT OF SOCIAL CONTRACT IN THE COORDINATES OF A MARKET ECONOMY - Gerasymova, Е (Proceedings of the National Aviation University Series Philosophy Cultural, 2020)
Introduction states that the condition of cardinal changes in the system of social and economic structures and transition to mechanisms of functioning of modern knowledge economy, the subject of research of theoretical and methodological bases of modern comprehension and practical application of humanitarian possibilities of the theory of the social contract and joint action within the international social experience remains undoubtedly actual. The aim of the article is to determine the development and substantiation of the concept of forming a social contract in the system of modern knowledge economy based on the recognition of the priority of universal values in the global coordinate system of the market economy. The socio-cultural approach methodology was used to demonstrate the process of expanding the content and practical application of such methodological principles as polyphony and dialogism as the creation of a semantic space of coexistence of thoughts and cognitive creativity. The methods of comparative analysis, structural, system-logical, analytical, synthetic methods were applied. Research results substantiate that the socio-philosophical analysis of the concept of free contract and fair price is carried out. Discussion deals with the research results of the philosophers and scientists such as K. Arrow, M. Gilbert, J. Buchanan, L. Mises, S. Mocherny, R. Harre. The differences between the results obtained by the author of the article and the indicated researchers are shown. Conclusion indicates that the problem of freedom of choice and necessity of existence of economic ethics, coordination of social and ethical limits of development of capitalist relations are determined. It is argued that the theory of modern capitalism must be supplemented by the theory of social genesis and the normative substantiation of the process of consumer taste formation. This is the question of social psychology and ethics as well as the theory of social institutions and the theory of political correction of certain defects of the modern post-industrial mode of production.